Development of the A-Grit Scale: Measuring Persistence in The Academic Context - Gunawan, Dyah Ayu Kusumawardani; Sin, Gabrielle Sinata; Gunawan, Dyah Ayu Permatasari; Gunawan, Goey Adi Widjaja (Universitas Ahmad Dahlan, 2025)
The intense academic competition and increasing learning demands in Indonesia highlight the need for a culturally and educationally appropriate measure of academic perseverance, or academic grit. This study aims to develop and validate A-GRIT, an instrument designed to assess Indonesian students’ academic grit through three key dimensions: Passion, Self-Control, and Growth Mindset. A total of 395 students aged 12 to 22 participated in the study, recruited through accidental sampling. Both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) supported the three-factor structure of A-GRIT, with a KMO value of 0.833 and acceptable goodness-of-fit indices (RMSEA < 0.05, CFI > 0.90, GFI > 0.95). Reliability testing yielded a Cronbach’s alpha of 0.821, indicating high internal consistency. These findings support A-GRIT as a valid and reliable instrument for assessing academic grit among Indonesian students and provide valuable insights for educational interventions aimed at enhancing student perseverance and academic achievement.